The Influence of Work Discipline on Employee Work Productivity at PT Triyanto Sukses Mandiri Sumedang - Muhammad Irfan Nur’arif; Marlina Septiani (CV. Ulil Albab Corp, 2024)
One way to increase employee work productivity is to increase the employee's own work discipline. Therefore, this research aims to determine and analyze the significant influence of work discipline on employee work productivity at PT. Triyanto Sukses Mandiri Sumedang. The research method used is a quantitative approach. The population used is employees of PT. Triyanto Sukses Mandiri Sumedang. The sampling technique in this research used nonprobability sampling. The number of samples used in this research was 45 respondents. Research data was analyzed using normality tests, simple regression analysis, linearity analysis, correlation coefficient, coefficient of determination, and hypothesis testing (t test). The research results show that work discipline and employee work productivity at PT Triyanto Sukses Mandiri Sumedang have a moderate relationship. This is proven by the correlation coefficient obtained at 0.573, furthermore, work discipline (X) influences work productivity (Y). This is proven by the results of the calculation of the coefficient of determination showing that the value of the coefficient of determination obtained is 0.328 or 32.8%. And there is a positive influence between work discipline (X) on work productivity (Y) which is obtained from the results of hypothesis testing which shows a t_count value of 4,588 > t_table 2,017.